Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.5296/ijhrs.v4i3.6368
|View full text |Cite
|
Sign up to set email alerts
|

Total Quality Management in Higher Education: A Review

Abstract: Total Quality Management (TQM) is a perception, which educational institutions can only attain through long period of planning, by the formulation and execution of annual quality program, which substantially moves towards the accomplishment of the vision. Application of TQM concepts is one of such degree, which will go a long way in reviving the higher education system. This study endeavors to analyze TQM in higher education and outline the literature on Critical Success Factors (CSF) and its execution in all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 27 publications
2
7
0
3
Order By: Relevance
“…Improvement of quality services (Farooq et al, 2007;Ali & Shastri, 2010;Zakuan et al, 2012;Todorut, 2013;Zabadi, 2013;In'airat & Al-Kassem, 2014), more efficient operations and improvement (Zakuan et al, 2012;Todorut, 2013;Zabadi, 2013) and perceived corporate picture (Zakuan et al, 2012) are some benefits which are confirmed in this study. Moreover, the advantage over other organizations (Zakuan et al, 2012;Zabadi, 2013;In'airat & Al-Kassem, 2014) is an important positive result of QM practices that in this study was referred to as an advantage over other HEIs in responding to the limited funding.…”
Section: Benefits Of Qm Practicessupporting
confidence: 75%
See 2 more Smart Citations
“…Improvement of quality services (Farooq et al, 2007;Ali & Shastri, 2010;Zakuan et al, 2012;Todorut, 2013;Zabadi, 2013;In'airat & Al-Kassem, 2014), more efficient operations and improvement (Zakuan et al, 2012;Todorut, 2013;Zabadi, 2013) and perceived corporate picture (Zakuan et al, 2012) are some benefits which are confirmed in this study. Moreover, the advantage over other organizations (Zakuan et al, 2012;Zabadi, 2013;In'airat & Al-Kassem, 2014) is an important positive result of QM practices that in this study was referred to as an advantage over other HEIs in responding to the limited funding.…”
Section: Benefits Of Qm Practicessupporting
confidence: 75%
“…TQM has been exceedingly acknowledged and successfully implemented in many organizations, providing them with the advantage in international and in local markets through the creation of high quality services or products to satisfy the needs of the customers (Zakuan et al, 2012;In'airat & Al-Kassem, 2014). According to Zabadi (2013), there are potential benefits from TQM adoption such as maintenance competitiveness, emphasis on the market needs, elimination of inefficiencies, satisfaction of the demands of stakeholders, reduction of the cost of performance, increase of production capacity, high level of service quality excellence and high level in all areas of an organization.…”
Section: Benefits Of Qm Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings confirm a relevant research (Manola & Tsarouhas, 2010), which investigated the contribution of TQM tools to improve the quality of administrative services in a higher education institution and showed that the implementation of these tools could show problems, propose solutions and help define procedures that will be useful to improve the quality of the administrative services of a higher education institution. In addition, the above-mentioned findings of the present study confirm the findings of other relevant research, which focused on the study of the results of the implementation of various TQM tools and practices (Korre-Natsi, 2003;Quinn et al, 2009;Ali & Shastri, 2010;Nyaoga et al, 2010;Manola & Tsarouhas, 2010;Pilava, 2012;Antoniadou & Hatzipanayiotou, 2012;Zabadi, 2013;Oluseye et al, 2014;In'airat & Al-Kassem, 2014;Alzhrami et al, 2016;Saha, 2016) and confirmed the benefits of the implementation of them.…”
Section: Official Website Of the Departmentsupporting
confidence: 79%
“…Other studies focus on identifying the most important dimensions of the quality of provided services (Chua, 2004;Lagrosen et al, 2004;Tsinidou et al, 2010;Saberi et al, 2015;Tarí & Dick, 2016). Moreover, there are studies that focus on the results from the adoption of various TQM tools and practices (Korre-Natsi, 2003;Quinn et al, 2009;Ali & Shastri, 2010;Nyaoga et al, 2010;Manola & Tsarouhas, 2010;Pilava, 2012;Antoniadou & Hatzipanayiotou, 2012;Zabadi, 2013;Oluseye et al, 2014;In'airat & Al-Kassem, 2014;Alzhrani et al, 2016;Saha 2016). …”
Section: Introduction Of the Problemmentioning
confidence: 99%